Estimating glomerular filtration rate via cystatin C in preterm infants: a comparative analysis - Yesim Coskun; Ozlem Unay Demirel; Tevfik Bayram; Ipek Akman; Duygu Ovunç Hacihamdioglu (Indonesian Pediatric Society, 2022)
Background: We aimed to determine the course of serum creatinine (sCr), serum cystatin C (sCysC) and urine cystatin C (uCysC) levels and calculate estimated glomerular filtration rate (eGFR) by using sCr- and sCysC-based formulas in preterm infants in the first 28 days of life. Methods: A total of 52 neonates were included in this prospective study. According to gestational age (GA), the neonates were divided into three groups. Group 1 composed of neonates who were born â‰¤28 weeks (n=15), group 2 and 3 consisted of infants who were born 29-31 weeks (n=16) and 32-34 weeks (n=21), respectively. Blood and urine samples were obtained at the 24-48 hours of life and then weekly until 28th day of life. sCr- and sCysC-based formulas were applied to determine the value and course of eGFR. Results: sCr level was negatively correlated with GA (r=-0.36, p=0.014) but not with BW (r=-0.15, p=0.31). While sCr levels showed significant variations in all study groups on day 7, day 14, and day 21 however, sCysC did not differ by GA at any time-points. All study groups had significantly different uCysC levels, except day 28. eGFR results calculated with sCr-based formula were detected to be closer to inulin. Conclusion: In preterm infants, sCr seemed to be a more reliable marker than sCysC to calculate eGFR. Moreover, in the same population, uCysC levels may reflect renal maturation more than sCysC.